1988
DOI: 10.1111/j.1600-0560.1988.tb00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Eruptive vellus hair cyst and steatocystoma multiplex: two related conditions?

Abstract: Eruptive vellus hair cyst and steatocystoma multiplex are infrequent lesions. Although there are clinical similarities between both entities, histologic features are distinctive. Especially noteworthy is the presence of sebaceous glands within the cyst wall of steatocystoma. We describe herein a patient with a familial monomorphous papular eruption on the forehead, biopsies from which showed features of both eruptive vellus hair cyst and steatocystoma multiplex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 19 publications
0
28
0
2
Order By: Relevance
“…The biopsies of the mother’s cysts revealed the typical features of steatocystoma in the biopsy taken from one of the larger cysts located in the trunk and features of EVHC in the biopsy taken from one of the cysts of the face. The association of a sebaceous gland near the cyst, as observed in this case, has previously been described in EVHC [7], but some authors have suggested that cysts with these histopathologic features might be considered ‘hybrid cysts’ with features of both SM and EVHC [8, 9, 10, 11]. …”
Section: Discussionmentioning
confidence: 87%
“…The biopsies of the mother’s cysts revealed the typical features of steatocystoma in the biopsy taken from one of the larger cysts located in the trunk and features of EVHC in the biopsy taken from one of the cysts of the face. The association of a sebaceous gland near the cyst, as observed in this case, has previously been described in EVHC [7], but some authors have suggested that cysts with these histopathologic features might be considered ‘hybrid cysts’ with features of both SM and EVHC [8, 9, 10, 11]. …”
Section: Discussionmentioning
confidence: 87%
“…EVHC mostly develop as a consequence of occlusion of the infundibulum of vellus hairs with resultant cystic dilatation and retention of keratinous debris and vellus hairs. The characteristic histology is that of a mid-dermal cyst containing laminated keratin and many vellus hairs 4 . Although milia and EVHC are distinct from one another, in our case, milia and EVHC were revealed Pilosebaceous Cysts with Apocrine Hidrocystoma: Same Disease Process?…”
Section: Discussionmentioning
confidence: 99%
“…Steffen and Ackerman |24| stated that'we do not consider eruptive hair cyst to be an entity sui generis or a hybrid but simply a steatocystoma', that the cystic formations in the patients examined by Urbina González et al [6], Sánchez et al [7], Sexton and Mur dock [9] and Requena and Sánchez Yus [23] are 'just alluded to as steatocystoma alone.…”
Section: Discussionmentioning
confidence: 99%
“…a clinically similar but histologically different entity, was first men tioned in 1977 15 1. Recently, several reports have presumed that at least in some patients both cysts can be seen or that the cysts may show histological features of both cysts [6][7][8][9][10], We describe a female patient who showed both types of cysts within one lesion. …”
Section: Introductionmentioning
confidence: 99%